2011
DOI: 10.1097/moo.0b013e32834cd54a
|View full text |Cite
|
Sign up to set email alerts
|

Management of pediatric orbital cellulitis and abscess

Abstract: Periorbital complications of sinusitis in pediatric patients often respond to medical therapy but may require surgical intervention to prevent serious complications. Continuous in-house evaluation of patients is necessary to observe for progression of symptoms and to optimize outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
93
0
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(104 citation statements)
references
References 20 publications
3
93
0
8
Order By: Relevance
“…In children, the periosteum at the medial orbital wall is loosely attached to the underlying lamina papyracea (Reid 2004). A recent review of cases of pediatric subperiosteal abscess suggested that immediate surgical intervention is not always the best treatment option (Bedwell and Bauman 2011;Bedwell and Choi 2013). Patients presenting with advanced ophthalmologic findings (impaired visual acuity, elevated intraocular pressure, ophthalmoplegia, proptosis ≥ 5 mm) or with large abscesses (width > 10 mm) are best treated surgically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In children, the periosteum at the medial orbital wall is loosely attached to the underlying lamina papyracea (Reid 2004). A recent review of cases of pediatric subperiosteal abscess suggested that immediate surgical intervention is not always the best treatment option (Bedwell and Bauman 2011;Bedwell and Choi 2013). Patients presenting with advanced ophthalmologic findings (impaired visual acuity, elevated intraocular pressure, ophthalmoplegia, proptosis ≥ 5 mm) or with large abscesses (width > 10 mm) are best treated surgically.…”
Section: Discussionmentioning
confidence: 99%
“…Conventionally, emergency endoscopic sinus surgery combined with intravenous antibiotics is the first choice for the treatment of suspected abscess (Eviatar et al 2008;Sultész et al 2009;Kinis et al 2013). However, immediate surgical intervention may not always be necessary for subperiosteal abscess (Bedwell and Bauman 2011;Bedwell and Choi 2013). Orbital subperiosteal hematoma is rare and occurs most often after trauma (Dobben et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…MRI is also important in the assessment of complications due to sinus infections such as cavernous sinus thrombosis. For the diagnosis, follow-up of treatment, and possible complications of acute rhinosinusitis, as well as for surgical planning of the cases considered, PNSCT is a frequently used imaging method with high sensitivity (7)(8)(9)(10)(11)(12). In particular, the location and extent of infection during acute rhinosinusitis is important.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in the literature, the medical treatment for cases of suspected orbital complications of acute sinusitis is ampicillinsulbactam, cefuroxime, ceftriaxone, cefotaxime, or clindamycin and the necessity of the medical treatment administration for 4-8 weeks is highlighted (7)(8)(9)(10)(11)(12)(13)(14). In our study, for preseptal cellulitis, we administered intravenous (IV ) 4×1.5 g of ampicillin-sulbactam (adult dose 3-4×1.5-3 g/day, pediatric dose 150 mg/kg [50 mg sulbactam and ampicillin] in children); for subperiosteal abscess, a combination of IV 4×1.5 g ampicillinsulbactam and ornidazole (adult dose 2×500 mg/day, pediatric dose 2 doses of 25 mg/kg/day); and for orbital abscess, IV ceftriaxone 2×1 g (adult dose 1-2 g/day, pediatric dose 50-75 mg/kg/day) -ornidazole 2×500 mg (adult dose 2×500 mg/ day, pediatric dose 2 doses of 25 mg/kg/day).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation